A major pathway for carbon and nitrogen losses — Gas emissions during storage of solid pig manure in China - Nan SHAN; Hu LI; Jian-zheng LI; Ee Ling Ng; Yan MA; Li-gang WANG; Qing CHEN (Journal of Integrative Agriculture, 2019)
This study investigated the carbon (C) and nitrogen (N) gas emissions (N2O, NH3, CO2 and CH4) from solid pig manure management in China. Gas emissions were quantified from static piles over 60 days during summer in China's Yangtze River Basin, using Drager-Tube and static chamber-gas chromatography techniques. High emissions of NH3 and N2O were observed at the early stage of storage, but high emission of CH4 occured later during storage. Overall, 62% of the total C in the original pile was lost; CO2 and CH4 emissions accounted for 57 and 0.2% of C lost respectively. Over the same time, 41% of the total N in the original pile was lost; NH3 and N2O emissions accounted for 15 and 0.3% of N lost respectively. The volatilization of NH3 during storage in summer was 4.56 g NH3 per kg dry weight. The total greenhouse gas (GHG) emissions during storage accounted for 67.93 g CO2 equivalent per kg dry weight; N2O and CH4 contributed to 46 and 55% of total GHG emissions respectively. Given China's major role in pig production, further attention should given to pig manure management to mitigate its contribution to atmospheric pollution.